Prediction of Slagging and Fouling Potential of Alternative Biomass Fuel as a Bagasse Substitute in Sugar Mill Boilers - Yunaidi, Yunaidi; Harnowo, Saptyaji (ASEAN Journal of Chemical Engineering, 2025)
Boilers in sugar mills are generally designed to use bagasse as a biomass fuel. In their operations, some sugar mills are unable to provide sufficient bagasse for boiler fuel due to milling conditions that fall below their normal capacity, so they must supplement their fuel sources with biomass fuels other than bagasse, such as rice husk, wood, and sawdust. This situation can impact the performance of sugar mill boilers, which are designed specifically for use with bagasse fuel, as each biomass type has distinct characteristics. The results indicate that the use of rice husk biomass as an alternative fuel will not pose serious problems associated with slagging and fouling, as it has a low potential risk for these issues. However, the use of mahogany, acacia, or mixed wood biomass may increase the risk of slagging and fouling in boiler equipment. This is confirmed by the analysis of the ash residue contained in the boiler superheater pipe of the sugar mill taken as a research object, which shows the presence of high slagging indicators, including the parameters of base to acid ratio (B/A), iron content in ash, Fe+Ca, silica content, and silica to alumina ratio (S/A), as well as high fouling indicators in ash characterized by high total alkali parameters, fouling index, and sodium content in ash.